Acerca del rigor metódico en la gnoseología de Leonardo Polo - Arce Delgado, Stanley (2011)
Leonardo Polo ́s method is shown as a constitutive aspect of gnoseology as a rigorous philosophical discipline. This work approaches some of the difficulties of polian gnoseology that could weaken its methodical rigor. Furthermore, it is argued that some of these difficulties come out of the misinterpretation of Polo ́s ideas.